Enhancing the phosphorescence of hybrid metal halides through molecular sensitization. Issue 32 (11th July 2019) - Gong, Liao-Kuo; Li, Jian-Rong; Wu, Zhao-Feng; Hu, Bing; Wang, Ze-Ping; Shen, Nan-Nan; Hu, Qian-Qian; Deng, Zhong-Hua; Zhang, Zhi-Zhuan; Fu, Jing-Jing; Du, Ke-Zhao; Huang, Xiao-Ying
Abstract : The room-temperature phosphorescence quantum efficiency of [BPy]6 [Pb3 Br12 ] has been improved by a maximum of fourteen-fold through sensitization of thiadiazole-based molecules. Abstract : Herein, a zero-dimensional (0D) hybrid organic–inorganic metal halide (OIMH) [BPy]6 [Pb3 Br12 ] (BPB, BPy = N -butylpyridinium) as a room-temperature phosphorescent (RTP) material is synthesized. Through molecular sensitization, its RTP quantum efficiency can be increased by a maximum of 14-fold. A white-light-emitting device is obtained via a solvent-free and eco-friendly melting method.